2006
DOI: 10.3168/jds.s0022-0302(06)72579-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lameness in High-Producing Holstein Cows Housed in Freestall Barns in Minnesota

Abstract: A cross-sectional study was conducted to estimate the prevalence of clinical lameness in high-producing Holstein cows housed in 50 freestall barns in Minnesota during summer. Locomotion and body condition scoring were performed on a total of 5,626 cows in 53 high-production groups. Cow records were collected from the nearest Dairy Herd Improvement Association test date, and herd characteristics were collected at the time of the visit. The mean prevalence of clinical lameness (proportion of cows with locomotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
217
13
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(281 citation statements)
references
References 21 publications
37
217
13
14
Order By: Relevance
“…This suggests that free stalls expose cattle to adverse environmental conditions, which are important to the epidemiology of lameness (Cook and Nordlund, 2009). The prevalence of lameness varies in the studies made in different countries of the world, ranging from 20% (Espejo et al, 2006) to 48% (Dippel et al, 2009) for loose housing systems and from 1% to 21% in tied systems (Cook, 2003;Sogstad et al, 2005, Zurbrigg et al, 2005. In Romania data are available only for the lameness prevalence in tie-stall housing and it is similar with that obtained in this study (Popescu et al, 2010b).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that free stalls expose cattle to adverse environmental conditions, which are important to the epidemiology of lameness (Cook and Nordlund, 2009). The prevalence of lameness varies in the studies made in different countries of the world, ranging from 20% (Espejo et al, 2006) to 48% (Dippel et al, 2009) for loose housing systems and from 1% to 21% in tied systems (Cook, 2003;Sogstad et al, 2005, Zurbrigg et al, 2005. In Romania data are available only for the lameness prevalence in tie-stall housing and it is similar with that obtained in this study (Popescu et al, 2010b).…”
Section: Resultssupporting
confidence: 85%
“…In Romania data are available only for the lameness prevalence in tie-stall housing and it is similar with that obtained in this study (Popescu et al, 2010b). The increase in lameness prevalence is associated with solid concrete flooring, slippery walking alleys (Cook and Nordlund, 2009), uncomfortable and dirty barns (Cook, 2002(Cook, , 2003Espejo et al, 2006;Chapinal et al, 2013), increased degree of dirtiness in cows' hind legs (Cook, 2002;Zurbrigg et al, 2005) and zero-grazing (Haskell et al, 2006). Because in our study the mean prevalence of lameness exceeds 15%, we can state, referring to Nordlund et al (2004) that the implementation of specific measures is urgently needed to decrease lameness in 67% of the evaluated farms.…”
Section: Resultsmentioning
confidence: 63%
“…Similar to mastitis and as described in literature, lameness incidence was found to increase with parity (Barkema et al, 1994;Espejo et al, 2006). Incidences of the first lameness events were highest in the 1st month of lactation and during the first 4 months of the year, January to April.…”
Section: Genetics Of Fitness Traits In Dairy Cowssupporting
confidence: 85%
“…Lameness, defined as a deviation in gait resulting from pain or discomfort from hoof or leg injuries and disease, can affect many cows (some studies have reported prevalence of up to 55%; Clarkson et al, 1996), reduces milk production, feed intake and fertility and is costly for producers (Green et al, 2002;O'Callaghan, 2002;Hernandez et al, 2005). Most gait evaluations assess changes relative to 'normal gait', but such changes can be difficult to judge; Whay et al (2003) reported that producers identified only one of every four cases of dairy cattle with hoof injuries or disease, and another study found that only one of every three cows were correctly identified (Espejo et al, 2006). The stoic nature of cattle means that even painful pathologies of the hoof or leg may cause little or no obvious changes in behaviour, and some pathologies such as heel erosion may cause little pain, at least in early stages of development.…”
Section: Introductionmentioning
confidence: 99%